A Theoretical and Experimental Research on the Influence of FDM Parameters on Tensile Strength and Hardness of Parts Made of Polylactic Acid - Zisopol, D. G.; Nae, I.; Portoaca, A. I.; Ramadan, I. (Engineering, Technology & Applied Science Research, 2021)
Fused Deposition Modeling (FDM) is a rapid prototyping method, widely used in the manufacture of plastic parts with complex geometric shapes. The quality of the parts manufactured by this process depends on the plastic material used and the FDM parameters. In this context, this paper will present the results of a theoretical and experimental research on how FDM parameters influence the tensile strength and hardness of samples made of PLA (Polylactic Acid).